Casting process for eliminating shrinkage porosity of large bearing
Through a variety of heat treatment and sandblasting treatment technologies, the problem of shrinkage during the casting of large bearings is solved, the hardness and wear resistance of bearings are improved, the service life is extended, and the stability is enhanced, and it is adapted to complex working conditions.
Patent Information
- Application Number
- CN202411445149.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The shrinkage problem caused by inconsistent cooling speed during the casting process of large bearings leads to reduced mechanical strength, hardness and wear resistance, affecting service life and reliability, and may cause problems of vibration, noise and lax sealing.
Using various heat treatment methods such as high-temperature smelting, annealing, sandblasting, arc spraying molybdenum carbide coating, normalization, quenching and tempering, combined with the grinding and polishing of sandblasting materials, a uniform surface roughness is formed to improve the coating. Adhesion and material properties.
It significantly improves the hardness, wear resistance and corrosion resistance of the bearing, extends the service life, reduces the occurrence of shrinkage, ensures the stability and reliability of the bearing, and adapts to high loads and complex working conditions.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of bearing casting and relates to a casting process for eliminating shrinkage of large bearings. Background Art
[0002] During the casting process of large bearings, the cooling speed of various parts of the casting is inconsistent, resulting in heat concentration in the thick center or geometric hot spots. Finally, when solidifying, the shrinkage is not fully compensated and shrinkage is formed. Shrinkage will cause the internal structure of the bearing to be loose, reduce its mechanical strength, hardness and wear resistance, and affect the service life and reliability of the bearing; the gaps caused by shrinkage may become stress concentration points during the operation of the bearing, aggravate the generation of vibration and noise, and reduce the running stability of the equipment; for bearings that need to be sealed, shrinkage may lead to loose sealing, causing lubricating oil or grease to leak, affecting the lubrication effect and running stability of the bearing; under extreme working conditions, shrinkage may cause bearing breakage or failure, causing equipment shutdown or even safety accidents, posing a threat to personnel and property.
[0003] Improper riser settings and unreasonable pouring systems during the preparation process artificially create hot spots, which increase the risk of shrinkage. In addition, the solidification characteristics, gas content and oxides of the material can also cause shrinkage. Summary of the invention
[0004] The purpose of the present invention is to provide a casting process for eliminating shrinkage of large bearings, which has the characteristics of high hardness and long service life of the produced bearings.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A casting process for eliminating shrinkage of large bearings, the specific process of the casting process is as follows:
[0007] S1: placing the bearing raw material into a high-temperature melting furnace for melting treatment at a temperature of 1350-1400°C for 20-30 minutes, placing the melted raw material into a mold, and obtaining a bearing blank after cooling;
[0008] S2: heating the bearing blank to 820-850°C for 3-4 hours, performing annealing treatment, and cooling to room temperature;
[0009] S3: performing surface sandblasting on the bearing blank after annealing, arc spraying a layer of molybdenum carbide coating on the surface of the bearing blank after sandblasting, and then performing surface polishing;
[0010] Among them, the preparation method of the sandblasting material used for sandblasting is as follows:
[0011] S3.1: Mix brown corundum, steel sand and glass beads in a mass ratio of 1:3:0.5, put them into a ball mill and grind them at a speed of 400-500 r / min for 3-5 h;
[0012] S3.2: washing the mixture obtained by grinding in S3.1 with deionized water, and drying at 110° C. for 24 hours after washing to obtain the sandblasting material;
[0013] S4: heating the polished bearing blank to 900-960° C. for normalizing, with a constant temperature treatment time of 4-6 hours, blowing the bearing blank with nitrogen, and slowly cooling it to room temperature;
[0014] S5: heating the bearing blank after normalizing treatment to 860-880°C for quenching treatment, the constant temperature treatment time is 1-2h, placing it in cooling water to quickly cool it down, and after cooling, using 70°C nitrogen to purge until the surface of the bearing blank is dry, and the purge flow rate of nitrogen is 10m / s;
[0015] S6: heating the quenched bearing blank to 300-380° C. for tempering, with a constant temperature treatment time of 1-2 hours, and then using nitrogen to evenly blow the surface of the bearing blank to slowly cool it to room temperature to obtain the bearing.
[0016] Furthermore, the bearing material in S1 is one of chromium-molybdenum steel and nickel-chromium-molybdenum steel.
[0017] Furthermore, the parameters of the sandblasting treatment in S3 are a sandblasting distance of 50 to 70 mm and a sandblasting angle of 60 to 80°.
[0018] Furthermore, the particle size of the sandblasting material in S3 is 200 mesh.
[0019] Furthermore, the arc spraying parameters in S3 are: the diameter of the molybdenum carbide nanowire is 200 nm, the spraying voltage is 30 V, the spraying current is 200 A, the spraying distance is 150 mm, and the compressed air pressure is 0.4 MPa.
[0020] Furthermore, the polishing parameters in S3 are: firstly, a 1000-mesh elastic module is used for treatment at 0.3-0.5 MPa for 0.5-1 h, and then a 2000-mesh elastic module is used for treatment at 0.5 MPa for 0.5 h.
[0021] Furthermore, the flow rate of the nitrogen purge in S4 is 10 m / s.
[0022] Furthermore, the slow cooling rate in S4 is 3°C / min.
[0023] Furthermore, the purge flow rate of nitrogen in S6 is 20 m / s.
[0024] Furthermore, the rate of slowly cooling to room temperature in S6 is 5°C / min.
[0025] After obtaining the blank, the present invention first eliminates casting stress through annealing, refines the grains, and improves the processing performance and use performance of the material. Annealing helps to improve the plasticity and toughness of the bearing blank and reduce the risk of deformation and cracking caused by casting stress. The bearing blank after annealing is then subjected to surface sandblasting, followed by arc spraying of a layer of molybdenum carbide coating, and surface polishing. Sandblasting increases surface roughness and improves coating adhesion; arc spraying of molybdenum carbide coating enhances wear resistance and corrosion resistance, sandblasting provides a good adhesion foundation for the coating, and the molybdenum carbide coating significantly improves the wear resistance and corrosion resistance of the bearing and extends its service life; the polished bearing blank is heated to 900-960°C for normalizing. Normalizing can refine the grains, increase the strength and hardness of the material, improve cutting performance, and further improve the mechanical properties of the bearing, making it more suitable for bearing high loads and complex working conditions; the normalized bearing blank is heated to 860-880°C for The bearing is then quenched to obtain a martensitic structure with high hardness and wear resistance, which significantly improves the hardness and wear resistance of the bearing and enables it to better adapt to high-load and high-speed operation conditions. Finally, the quenched bearing blank is heated to 300-380°C for tempering. The tempering treatment eliminates the quenching stress, stabilizes the structure, obtains good comprehensive mechanical properties, avoids deformation and cracking caused by quenching stress, and maintains high hardness and wear resistance, ensuring the stability and reliability of the bearing. The bearings made by this casting process are not prone to shrinkage and have a longer service life.
[0026] Sandblasting can form a uniform roughness on the surface of the bearing blank, which is crucial for the subsequent coating adhesion. The molybdenum carbide coating needs to adhere to a surface with a certain roughness to ensure a stronger bond between the coating and the substrate, thereby improving the durability of the coating; sandblasting can thoroughly remove impurities such as grease, dirt, oxide scale, etc. on the surface of the bearing blank, making the surface cleaner and providing a good base for subsequent coating spraying. A clean surface helps reduce bubbles and defects in the coating and improves the quality of the coating; the surface roughness increased by sandblasting can significantly increase the mechanical bite force between the molybdenum carbide coating and the bearing blank, thereby making the coating more firmly attached to the substrate. This helps prevent the coating from flaking or falling off during use and extends the service life of the bearing.
[0027] The mixed use of brown corundum, steel grit and glass beads can give full play to their respective advantages and improve the overall performance of sandblasting. The high hardness and good cutting ability of brown corundum can remove stubborn dirt; the moderate hardness and toughness of steel grit can maintain the cleaning effect while avoiding excessive damage; the light weight and environmental protection characteristics of glass beads can form a high-smooth surface. After grinding in a ball mill, the mixed sandblasting material has a uniform particle size, which can form a uniform impact effect during the sandblasting process, improving the uniformity and consistency of surface treatment.
[0028] Molybdenum carbide (MoC) has extremely high hardness and good wear resistance. Spraying a molybdenum carbide coating on the bearing surface can significantly enhance the wear resistance of the bearing surface and extend the service life of the bearing; the molybdenum carbide coating also has good corrosion resistance and can resist the erosion of various corrosive media, protecting the bearing matrix from corrosion damage, thereby maintaining the stability and reliability of the bearing. The hardness and wear resistance of the molybdenum carbide coating improve the overall structural stability of the bearing, making the bearing less likely to deform or damage during operation, thereby reducing the possibility of shrinkage expansion or new shrinkage caused by structural problems. By improving wear resistance and corrosion resistance, the molybdenum carbide coating significantly extends the service life of the bearing. During long-term use, the bearing can better maintain its original size and shape accuracy, reducing dimensional changes and performance degradation caused by wear and corrosion.
[0029] The present invention combines the four heat treatment methods of annealing, normalizing, quenching and tempering. Annealing helps to eliminate or reduce the internal stress and structural defects generated in the bearing blank during the casting process, making the material structure more uniform, and laying a good foundation for subsequent processing and heat treatment; normalizing can further refine the grains, improve the strength and toughness of the material, and reduce the expansion tendency of defects such as shrinkage; quenching can rapidly cool the bearing blank to obtain a high-hardness martensitic structure, significantly improving the hardness and wear resistance of the bearing; tempering reduces brittleness, improves plasticity and toughness while maintaining a certain hardness, so that the bearing has more balanced mechanical properties and meets the use requirements under complex working conditions.
[0030] Beneficial effects of the present invention:
[0031] (1) The present invention uses arc spraying of molybdenum carbide coating to enhance wear resistance and corrosion resistance. Sandblasting provides a good adhesion basis for the coating. The molybdenum carbide coating significantly improves the wear resistance and corrosion resistance of the bearing and prolongs its service life.
[0032] (2) The present invention combines the four heat treatment methods of annealing, normalizing, quenching and tempering to make the material structure more uniform. While maintaining a certain hardness, it reduces brittleness, improves plasticity and toughness, has better strength and toughness, and reduces the expansion tendency of defects such as shrinkage, so that the bearing has more balanced mechanical properties and meets the use requirements under complex working conditions. DETAILED DESCRIPTION
[0033] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0034] Example 1
[0035] S1: Put the chromium-molybdenum steel, the raw material of the bearing, into a high-temperature melting furnace for melting treatment at a temperature of 1350°C for 25 minutes, put the melted raw material into a mold, and obtain a bearing blank after cooling;
[0036] S2: heating the bearing blank to 830°C, keeping the temperature constant for 4 hours, performing annealing treatment, and cooling to room temperature;
[0037] S3: The bearing blank after annealing is subjected to surface sandblasting treatment, with a sandblasting distance of 60 mm and a sandblasting angle of 70°. After the sandblasting treatment, a layer of molybdenum carbide coating is arc sprayed on the surface of the bearing blank. The parameters of the arc spraying are: the diameter of the molybdenum carbide nanowire is 200 nm, the spraying voltage is 30 V, the spraying current is 200 A, the spraying distance is 150 mm, and the compressed air pressure is 0.4 MPa. The surface is then polished. The polishing parameters are: firstly, a 1000-mesh elastic module is used for treatment at 0.4 MPa for 0.5 h, and then, a 2000-mesh elastic module is used for treatment at 0.5 MPa for 0.5 h.
[0038] Among them, the preparation method of the sandblasting material used for sandblasting is as follows:
[0039] S3.1: brown corundum, steel sand and glass beads were mixed in a mass ratio of 1:3:0.5, and ground in a ball mill at a speed of 500 r / min for 3 h;
[0040] S3.2: The mixture obtained by grinding in S3.1 is washed with deionized water, and then dried at 110° C. for 24 hours to obtain the sandblasting material, wherein the particle size of the sandblasting material is 200 mesh;
[0041] S4: heating the polished bearing blank to 930°C for normalizing treatment, and the constant temperature treatment time is 5 hours. The bearing blank is purged with nitrogen at a flow rate of 10m / s, and slowly cooled to room temperature at a rate of 3°C / min.
[0042] S5: The bearing blank after normalizing treatment is heated to 870°C for quenching treatment. The constant temperature treatment time is 2 hours. The bearing blank is placed in cooling water for rapid cooling. After cooling, nitrogen gas at 70°C is used to purge the bearing blank until the surface is dry. The purge flow rate of nitrogen gas is 10 m / s.
[0043] S6: The quenched bearing blank is heated to 350°C for tempering, and the constant temperature treatment time is 1.5 hours. Then, nitrogen is evenly purged on the surface of the bearing blank to slowly cool it to room temperature at a rate of 5°C / min. The purging flow rate of nitrogen is 20m / s to obtain the bearing.
[0044] Example 2
[0045] S1: Put the chromium-molybdenum steel, a raw material of the bearing, into a high-temperature melting furnace for melting treatment at a melting temperature of 1400°C for 20 minutes, put the melted raw material into a mold, and obtain a bearing blank after cooling;
[0046] S2: heating the bearing blank to 820°C, keeping the temperature constant for 4 hours, performing annealing treatment, and cooling to room temperature;
[0047] S3: The bearing blank after annealing is subjected to surface sandblasting treatment, with a sandblasting distance of 50 mm and a sandblasting angle of 60°. After the sandblasting treatment, a layer of molybdenum carbide coating is arc sprayed on the surface of the bearing blank. The parameters of the arc spraying are: the diameter of the molybdenum carbide nanowire is 200 nm, the spraying voltage is 30 V, the spraying current is 200 A, the spraying distance is 150 mm, and the compressed air pressure is 0.4 MPa. The surface is then polished. The polishing parameters are: firstly, a 1000-mesh elastic module is used for treatment at 0.3 MPa for 1 h, and then a 2000-mesh elastic module is used for treatment at 0.5 MPa for 0.5 h.
[0048] Among them, the preparation method of the sandblasting material used for sandblasting is as follows:
[0049] S3.1: brown corundum, steel sand and glass beads were mixed in a mass ratio of 1:3:0.5, and ground in a ball mill at a speed of 400 r / min for 5 h;
[0050] S3.2: The mixture obtained by grinding in S3.1 is washed with deionized water, and then dried at 110° C. for 24 hours to obtain the sandblasting material, wherein the particle size of the sandblasting material is 200 mesh;
[0051] S4: heating the polished bearing blank to 900°C for normalizing treatment, and the constant temperature treatment time is 6 hours. The bearing blank is purged with nitrogen at a flow rate of 10m / s, and slowly cooled to room temperature at a rate of 3°C / min.
[0052] S5: The bearing blank after normalizing treatment is heated to 860°C for quenching treatment. The constant temperature treatment time is 2 hours. The bearing blank is placed in cooling water for rapid cooling. After cooling, nitrogen gas at 70°C is used to purge the surface of the bearing blank until it is dry. The purge flow rate of the nitrogen gas is 10 m / s.
[0053] S6: The quenched bearing blank is heated to 300°C for tempering, and the constant temperature treatment time is 2 hours. Then, nitrogen is evenly purged on the surface of the bearing blank to slowly cool it to room temperature at a rate of 5°C / min. The purging flow rate of nitrogen is 20m / s to obtain the bearing.
[0054] Example 3
[0055] S1: Put the raw material of the bearing, nickel-chromium-molybdenum steel, into a high-temperature melting furnace for melting treatment at a temperature of 1350°C for 30 minutes, put the melted raw material into a mold, and obtain a bearing blank after cooling;
[0056] S2: heating the bearing blank to 850°C, keeping the temperature constant for 3 hours, performing annealing treatment, and cooling to room temperature;
[0057] S3: The bearing blank after annealing is subjected to surface sandblasting treatment, with a sandblasting distance of 70 mm and a sandblasting angle of 80°. After the sandblasting treatment, a layer of molybdenum carbide coating is arc sprayed on the surface of the bearing blank. The parameters of the arc spraying are: the diameter of the molybdenum carbide nanowire is 200 nm, the spraying voltage is 30 V, the spraying current is 200 A, the spraying distance is 150 mm, and the compressed air pressure is 0.4 MPa. The surface is then polished. The polishing parameters are: firstly, a 1000-mesh elastic module is used for treatment at 0.5 MPa for 0.5 h, and then, a 2000-mesh elastic module is used for treatment at 0.5 MPa for 0.5 h.
[0058] Among them, the preparation method of the sandblasting material used for sandblasting is as follows:
[0059] S3.1: brown corundum, steel sand and glass beads were mixed in a mass ratio of 1:3:0.5, and ground in a ball mill at a speed of 500 r / min for 3 h;
[0060] S3.2: The mixture obtained by grinding in S3.1 is washed with deionized water, and then dried at 110° C. for 24 hours to obtain the sandblasting material, wherein the particle size of the sandblasting material is 200 mesh;
[0061] S4: heating the polished bearing blank to 960°C for normalizing treatment, and the constant temperature treatment time is 4 hours. The bearing blank is purged with nitrogen at a flow rate of 10 m / s, and slowly cooled to room temperature at a rate of 3°C / min.
[0062] S5: The bearing blank after normalizing treatment is heated to 880°C for quenching treatment. The constant temperature treatment time is 1 hour. The bearing blank is placed in cooling water for rapid cooling. After cooling, nitrogen gas at 70°C is used to purge the bearing blank until the surface is dry. The purge flow rate of nitrogen gas is 10m / s.
[0063] S6: The quenched bearing blank is heated to 380°C for tempering, and the constant temperature treatment time is 1 hour. Then, nitrogen is evenly purged on the surface of the bearing blank to slowly cool it to room temperature at a rate of 5°C / min. The purging flow rate of nitrogen is 20m / s to obtain the bearing.
[0064] Comparative Example 1
[0065] In this comparative example, no sandblasting was performed on the surface during the preparation process, and the remaining steps were consistent with those in Example 1.
[0066] Comparative Example 2
[0067] In the preparation process of this comparative example, a layer of molybdenum carbide coating is not arc sprayed on the surface, and the remaining steps are consistent with Example 1.
[0068] Comparative Example 3
[0069] This comparative example does not undergo normalizing treatment during the preparation process, and the remaining steps are consistent with those of Example 1.
[0070] Comparative Example 4
[0071] This comparative example does not undergo quenching during the preparation process, and the remaining steps are consistent with those of Example 1.
[0072] The surface wear resistance of the embodiment and the comparative example was tested according to GB / T 12444.1-1990; the hardness was tested according to GB / T230.1-2018, and the experimental results are summarized in the following table; the corrosion resistance test was carried out according to ISO 9227:2017, the sample was fixed, and the concentration of 10% sodium chloride was adjusted with 3% hydrochloric acid to a pH value of 3 to prepare brine, which was sprayed on the sample through a spray device, with a spray volume of 20 mL / s, a spray frequency of 60 min / time, each spray for 20 s, and continuous spraying for 72 h, and the corrosion of the sample was observed.
[0073] 100 revolutions mass loss / mg Hardness value HR Corrosion resistance Example 1 32.4 120 No corrosion, no bubbles Example 2 32.8 115 No corrosion, no bubbles Example 3 32.7 115 No corrosion, no bubbles Comparative Example 1 35.6 95 No corrosion or bubbles Comparative Example 2 38.5 95 corrosion Comparative Example 3 37.4 75 No corrosion, no bubbles Comparative Example 4 42.5 70 No corrosion, no bubbles
[0074] From the experimental data, it can be seen that sandblasting makes the coating and the blank more closely bonded, and the increase of the coating effectively improves the corrosion resistance of the bearing. Both normalizing and quenching treatments effectively improve the wear resistance and hardness of the bearing.
[0075] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A casting process for eliminating shrinkage of large bearings, characterized in that: The specific process of the casting process is as follows: S1: placing the bearing raw material into a high-temperature melting furnace for melting treatment at a temperature of 1350-1400°C for 20-30 minutes, placing the melted raw material into a mold, and obtaining a bearing blank after cooling; S2: heating the bearing blank to 820-850°C for 3-4 hours, performing annealing treatment, and cooling to room temperature; S3: performing surface sandblasting on the bearing blank after annealing, arc spraying a layer of molybdenum carbide coating on the surface of the bearing blank after sandblasting, and then performing surface polishing; Among them, the preparation method of the sandblasting material used for sandblasting is as follows: S3.1: Mix brown corundum, steel sand and glass beads in a mass ratio of 1:3:0.5, put them into a ball mill and grind them at a speed of 400-500 r / min for 3-5 h; S3.2: washing the mixture obtained by grinding in S3.1 with deionized water, and drying at 110° C. for 24 hours after washing to obtain the sandblasting material; S4: heating the polished bearing blank to 900-960° C. for normalizing, with a constant temperature treatment time of 4-6 hours, blowing the bearing blank with nitrogen, and slowly cooling it to room temperature; S5: heating the bearing blank after normalizing treatment to 860-880°C for quenching treatment, the constant temperature treatment time is 1-2h, placing it in cooling water to quickly cool it down, and after cooling, using 70°C nitrogen to purge until the surface of the bearing blank is dry, and the purge flow rate of nitrogen is 10m / s; S6: heating the quenched bearing blank to 300-380° C. for tempering, with a constant temperature treatment time of 1-2 hours, and then using nitrogen to evenly blow the surface of the bearing blank to slowly cool it to room temperature to obtain the bearing.
2. A casting process for eliminating shrinkage of large bearings according to claim 1, characterized in that: The bearing material in S1 is one of chromium-molybdenum steel and nickel-chromium-molybdenum steel.
3. A casting process for eliminating shrinkage of large bearings according to claim 1, characterized in that: The parameters of the sandblasting treatment in S3 are a sandblasting distance of 50 to 70 mm and a sandblasting angle of 60 to 80°.
4. A casting process for eliminating shrinkage of large bearings according to claim 1, characterized in that: The particle size of the sandblasting material in S3 is 200 mesh.
5. A casting process for eliminating shrinkage of large bearings according to claim 1, characterized in that: The arc spraying parameters in S3 are: the diameter of the molybdenum carbide nanowire is 200 nm, the spraying voltage is 30 V, the spraying current is 200 A, the spraying distance is 150 mm, and the compressed air pressure is 0.4 MPa.
6. A casting process for eliminating shrinkage of large bearings according to claim 1, characterized in that: The polishing parameters in S3 are: firstly, a 1000-mesh elastic module is used for treatment at 0.3-0.5 MPa for 0.5-1 h, and then a 2000-mesh elastic module is used for treatment at 0.5 MPa for 0.5 h.
7. A casting process for eliminating shrinkage of large bearings according to claim 1, characterized in that: The flow rate of nitrogen purge in S4 is 10 m / s.
8. The casting process for eliminating shrinkage of large bearings according to claim 1, characterized in that: The slow cooling rate in S4 is 3°C / min.
9. A casting process for eliminating shrinkage of large bearings according to claim 1, characterized in that: The purge flow rate of nitrogen in S6 is 20 m / s.
10. A casting process for eliminating shrinkage of large bearings according to claim 1, characterized in that: The rate of slowly cooling to room temperature in S6 is 5°C / min.
Citation Information
Patent Citations
Machining technology of high-strength wear-resistant guide rail steel
CN112410515A
High-wear-resistance high velocity oxy-fuel spraying chromium carbide-based coating and preparation method thereof
CN117210780A
Method for manufacturing a coating of MMC und component thereof
EP2045350A2